Tornar-se professor, professora: a constituição da identidade profissional de docentes que atuam no atendimento educacional especializado de escolas da rede municipal de Uberlândia – MG - Souza, Patrícia Resende de (2020)
This master's research is part of the line of research Knowledge and Educational Practices, of the Graduate Program in Education at the Federal University of Uberlândia, MG and has as object of study the constitution of the teaching identity of professionals who work in Specialized Educational Service (ESA). The research problem that guided the investigation was: What elements of the identity constitution are present in becoming a teacher and professor at (ESA) and how does the professional development of teachers to work at ESA occur? The general objective of the research was to understand becoming a teacher, the constitution of the teaching identity and the professional development of teachers who work in the ESA of schools in the Municipal Public Network of Uberlândia. The specific objectives were: to know, from the dialogue with the teachers, aspects of the life trajectory of the ESA professionals who contributed to the identification process and the choice of the teaching profession; identify how the construction of the teaching identity of the ESA occurs and the “becoming a teacher”, its social image, its “place” in the school space; identify and analyze the impacts of the legal frameworks of the history of Special Education in the constitution of the teaching identity and professional development of the teachers, with views to reaching a proposal for Inclusive Education. To support our study, we are guided by Almeida (2012); Campos (2001, 2017); Campos, Gaspar and Moraes (2020); Cunha (2010); Freire (1987; 1992; 1993; 1997; 2000; 2001; 2007; 2011; 2015); Imbernón (2011); Melo e Campos (2019); Nóvoa (1991, 1992, 2009); Pimenta (1996; 1999; 2002; 2008; 2009; 2010; 2011), among others who also affirm the need for training, specific knowledge of the professional for teaching in Education, a condition for the constitution of identity and professional development. We also used the authors Carlos (2007) and Cunha (2010) to realize the discussion about the meaning of the concepts of space and “place” and the contributions of Dubar (1997, 2005), Ciampa (1984, 1998), among others, to elucidate the concept and constitution of identity, teaching identity. For reflection on the composition of legal aspects, documents related to Special Education in Brazil were selected, based on their relevance in relation to the general theme of the research. Exploratory research with a qualitative approach contributed to achieve intellection with our object of study. The theoretical-methodological option, in conjunction with dialectical historical materialism, supported the definition of the categories of analysis and broadened our reflections on the concepts of special and inclusive education, identity, initial, continuous teacher training and professional teacher development. The research data were obtained through the analysis of documents from the SME of Uberlândia about the ESA and from an interview with six teachers who work in the ESA of the municipal network of Uberlândia. For the construction, interpretation of data and understanding of the research object, we used the content analysis technique proposed by Bardin (2011). From the dialogue with the teachers, we understand that teacher training, initial and permanent, is essential to the process of “becoming” a teacher; ESA, as a place understood as belonging, is the foundation of the identity constitution.